The Role Of Integrated Reporting In Emerging Market: Earnings Quality And Debt Maturity - Pria Aji Pamungkas; Amrie Firmansyah; Resi Ariyasa Qadri; Agung Dinarjito; Zef Arfiansyah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The maturity structure of debt can have financial and operational consequences for a firm as debt maturity is a key aspect of financial flexibility. Moreover, debt maturity can impact a firm's ability to undertake long-term productive investments and, as a result, affect economic activity. This study aims to examine the effect of earnings quality on debt maturity and the role of Integrated Reporting (IR) in moderating these effects. This study's methodology is a quantitative approach with multiple linear regression models and panel data. The sample employed in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX). The type of data employed in this study is secondary data sourced from financial statements and annual reports from 2016 to 2020. The sample selection using a purposive sampling method with the number of samples amounted to 595 firm-year observations. The results of this study suggest that earnings quality does not affect debt maturity. Additional tests show that income maximization companies tend to have shorter debt maturity. However, IR failed to moderate the effect of earnings quality on debt maturity. This study indicates that the Financial Services Authority (OJK) needs to conduct better monitoring and regulation to increase creditor protection through optimal debt policy disclosure from the companies.